Subversion of MAPK signaling by pathogenic bacteria (MAP Kinase, 2015)
Bacterial components are recognized by host pattern recognition receptors that trigger signaling cascades, leading to inflammation and eradication of the bacteria. The main proinflammatory signaling pathway is the MAP kinase (MAPK)/NF-κB interwoven cascades, which result in transcription of pro-inflammatory genes. Many bacteria have evolved to interfere with the immune response through a mechanism that involves delivery of virulent proteins to the host cells. These proteins posttranslationally modify key components in the host signaling cascades. This review will describe bacterial strategies to directly manipulate host MAPK signaling, summarizing recent discoveries in the field.
Keywords: MAPK signaling; pathogenic bacteria; host-pathogen interaction; toxins; effectors.